2008
DOI: 10.1007/s10677-008-9135-5
|View full text |Cite
|
Sign up to set email alerts
|

A Defense of a Particularist Research Program

Abstract: What makes some acts morally right and others morally wrong? Traditionally, philosophers have thought that in order to answer this question we must find and formulate exceptionless moral principles-principles that capture all and only morally right actions. Utilitarianism and Kantianism are paradigmatic examples of such attempts. In recent years, however, there has been a growing interest in a novel approach-Particularism-although its precise content is still a matter of controversy. In this paper I develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…of moral principles, but to certain intellectual capacities or skills that allow her to have insight into, or "see", what acting well would involve on a particular occasion (Hursthouse 2006, 284-85). Furthermore, Uri Leibowitz (2009Leibowitz ( , 2013 defines generalism as the view that exceptionless principles are necessary for explaining moral phenomena, and particularism as "a meta-theoretical commitment to the possibility of explaining moral phenomena ... without appealing to exceptionless moral principles" (Leibowitz 2013, 125). Since Aristotle"s comments, quoted above, show that he thinks it is possible to explain moral phenomena without appealing to exceptionless principles, and strongly suggest that there are no exceptionless principles that can determine appropriateness but only "rules of thumb" that are true for the most part, with what is appropriate to do in a given situation being particular to that situation, i.e.…”
Section: Aristotle's Account Of the Ethical Virtuesmentioning
confidence: 99%
“…of moral principles, but to certain intellectual capacities or skills that allow her to have insight into, or "see", what acting well would involve on a particular occasion (Hursthouse 2006, 284-85). Furthermore, Uri Leibowitz (2009Leibowitz ( , 2013 defines generalism as the view that exceptionless principles are necessary for explaining moral phenomena, and particularism as "a meta-theoretical commitment to the possibility of explaining moral phenomena ... without appealing to exceptionless moral principles" (Leibowitz 2013, 125). Since Aristotle"s comments, quoted above, show that he thinks it is possible to explain moral phenomena without appealing to exceptionless principles, and strongly suggest that there are no exceptionless principles that can determine appropriateness but only "rules of thumb" that are true for the most part, with what is appropriate to do in a given situation being particular to that situation, i.e.…”
Section: Aristotle's Account Of the Ethical Virtuesmentioning
confidence: 99%
“…For example, if most western countries that have been consistently ranked in the upper 20 percent of quality educators have researched and concluded that school leaders subscribe to a person specification, a role description, and an accredited training program to refine them into the good leaders, should that necessarily become a policy that Cameroon can borrow or learn? Having such a conclusion will be an endorsement that school leadership is an art as well as a science (Coughlan, 2019;Bryan, 2008;Leibowitz, 2009). From a universalist point of view, that every role, in humans that extend to the society, needs to be structured by rules, codes of practice, and laws which although enacted in one context, can easily be understood in another context.…”
Section: Theoretical Conceptualization: Particularism and Universalismentioning
confidence: 99%
“…However, this is good practice in which the higher appointment stems from productivity rather than personal relationships. Personal and family loyalty rather than the social contract theory remains a major policy determinant in Cameroon as far as our discussion on school leadership appointments is concerned (Leibowitz, 2009;Mungiu-Pippidi, 2005).…”
Section: Theoretical Conceptualization: Particularism and Universalismentioning
confidence: 99%
“…9.Lots of particularists and generalists suggest that moral principles link the descriptive and the normative (see, for instance, Little 2000; McNaughton 1988, 190–192; Leibowitz 2009, 184–185; Cullity 2002, 170–171; and Jackson, Pettit, and Smith 2000, 80–81). There’s an interesting question about how to characterize the difference between descriptive and normative terms.…”
Section: Notesmentioning
confidence: 99%